SQL for Beginners with Microsoft SQL Server Database - Batra, Anil (Packt Publishing, 2020)
Explore the fundamentals of SQL and Microsoft SQL Server and understand their role in the world of marketing and digital analytics About This Video Familiarize yourself with Microsoft SQL Server database fundamentals Gain the confidence to write flawless SQL queries Discover how to import and export data from SQL Server In Detail This video course will teach you how to extract data on your own and will give you the confidence to use SQL with Microsoft SQL Server to pull data for conducting marketing analysis without relying on anyone. The course begins with a brief introduction to SQL Server and its architecture and shows you how to install Microsoft SQL Server on your machine. Next, you'll walk through the process of finding data in the database, learn how to use SQL queries, join multiple tables, and aggregate the data. As you advance, you'll grasp the techniques used to manipulate data such as combining multiple columns and string values, extracting characters from strings, and finding the length of a string. Toward the end, you'll wrap up key SQL statements for inserting data in a table, updating records, and deleting records from a table, and get an overview of joins. By the end of this course, you'll be well-versed with the basics of SQL and be ready to use Microsoft SQL Server to add, extract, and manipulate data for making profitable marketing decisions.
Keywords: Electronic videos